Eating disorders in children and adolescents : a clinical handbook - Le Grange, Daniel; Lock, James (Guilford Press, 2011)
"Eating disorders typically first appear during childhood and adolescence. Despite this early age of onset, edited volumes on eating disorders have not focused on this age cohort. One of the primary purposes of this book is to redress this imbalance and target the unique issues that pertain to the development, assessment, and treatment of eating disorders in children and adolescents, a period of heightened vulnerability to the these disorders and to the potential damage they can cause"--Provided by publisher.